1995
DOI: 10.1111/j.1348-0421.1995.tb02245.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution of Adenoviruses, Enteroviruses and Reoviruses in Urban River Water

Abstract: In the 63-month period from January 1988 to March 1993, monthly levels of adenoviruses, enteroviruses (coxsackie B, polio, echo) and reoviruses in the urban river water in Nara Prefecture, Japan were in the range 0-25, 0-190 and 0-325, plaque forming units per liter (PFU/liter), and the average levels were 2.4, 40.6 and 56.2 PFU/liter, respectively. The peak reovirus level was found in winter during the cold weather months (Nov. to Mar.). The peak enterovirus level was found in summer (May to Sept.) but contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 18 publications
1
47
0
1
Order By: Relevance
“…In contrast to the notion that only those adenoviruses that infect the intestinal tract of the host will be excreted in feces, adenoviruses type 5, the nonenteric adenovirus strain that accounts for 11% of clinical adenovirus cases reported to World Health Organization, is also frequently detected in aquatic environments (93,151).…”
Section: Adenovirusesmentioning
confidence: 91%
“…In contrast to the notion that only those adenoviruses that infect the intestinal tract of the host will be excreted in feces, adenoviruses type 5, the nonenteric adenovirus strain that accounts for 11% of clinical adenovirus cases reported to World Health Organization, is also frequently detected in aquatic environments (93,151).…”
Section: Adenovirusesmentioning
confidence: 91%
“…It was reversely transcribed into enterovirus and reovirus cDNA, respectively. Enterovirus, reovirus, HAV, and adenovirus-specific primers were prepared based on the sequences reported previously (7,11,22). cDNA was amplified using each set of primer pairs for enterovirus (Et1 (ϩ) 5'-CCTCCGGCCCCTGAATG-3'/ Et2 (Ϫ) 5'-ACCGGATGGCCAATCCAA-3'), HAV (HAV1 (ϩ) 5'-CAGCACATCAGAAAGGTGAG-3'/ HAV2 (Ϫ) 5'-CTCCAGAATCATCTCCAA-3'), and adenovirus (A1 (ϩ) 5'-GCCCCAGTGGTCTTACATGCACATC-3'/ A2 (Ϫ) 5'-CAGCACGCCGCGGATGTCAAAGT-3') in DNA thermal cycler 480 (Perkin Elmer Cetus, Norwalk, Conn., U.S.A.) for 33 cycles.…”
Section: Methodsmentioning
confidence: 99%
“…While most virus-monitoring methods mainly target enteroviruses in water samples, we targeted reoviruses as well as other enteric viruses, including adenoviruses and HAV (20,21). Reoviruses are known to be present in water in greater numbers than enteroviruses, and have been frequently detected in surface waters either alone or associated with enteroviruses (22).…”
mentioning
confidence: 99%
“…Polioviruses, coxsackievirus A and B, and echoviruses have been found in rivers (e.g., Payment et al, 1988;Miyama et al, 1992;Tani et al, 1995), but coxsackievirus A and B and echoviruses have also been reported in lakes (D'Alessio et al, 1981) and swimming pools (Kee et al, 1994). Sources of waterborne enteroviruses suggested in the scientific literature include sewage (Oostvort et al, 1994;Van der Avoort et al, 1995), storm sewer discharge and runoff (D'Alessio et al, 1981), human activities (Payment et al, 1988;Kee et al, 1994), and diapers and sullage (Field et al, 1968).…”
Section: Occurrencementioning
confidence: 99%